Evaluation of Flexural Strength and Impact Strength of CAD/CAM and Heat Cured Acrylic Resin Modified by Zinc Oxide Nanoparticles - Mustafa Nabeel Al-Shakarchi; Radhwan H Hasan (University of Mosul, College of Dentistry, 2023)
Aims: To analyse the effects of the incorporation of Zinc Oxide nanoparticles (ZnO NPs) with actual size (10-30 nm) at one concentration (1%) and compare it with milling CAD/CAM and non-modified heat cure denture base materials on the flexural strength and impact strength. Materials and methods: samples' number were 60, which was divided into thirty specimens for each test and sub-grouped into 10 for each group (control, 1 % ZnO NPs, CAD/CAM). Using the SPSS program, the statistical analysis was carried out using ANOVA, descriptive statistics, and Duncan's test at a significant p ≤ 0.05. Results: The findings showed a substantial difference between the groups. Moreover, milled CAD/CAM PMMA material had the highest flexural strength and impact strength than groups. Morever, Flexural strength and impact strength for the PMMA-ZnO nanocomposite at ZnO nanoparticles (1%) increased significantly, when compared to control. Conclusions: For edentulous patients, milled CAD/CAM dentures are more suitable because of their improved mechanical properties. in addition, that use of ZnO nanoparticles as dental fillers at 1% by weight significantly increased the PMMA denture base material's flexural and impact strength.